Agama Ekologis dan Wacana Non-Human Turn - Khasri, Muhammad Rodinal Khair; Ilyas, Ali (Divinitas Jurnal Filsafat dan Teologi Kontekstual, 2024)
This article discusses the difference between posthuman discourse and nonhuman discourse in the context of ecological religion. Unlike posthuman discourse, which has teleological elements, nonhuman discourse emphasizes that humans interact with nonhuman entities without seeking the transformation of humans into non-humans. The article proposes that it is important to understand the relationship between humans and nature as a nonhuman agency, rather than merely as nonhuman entities. This is aimed at reconstructing the ontological basis of ecological religious discourse to avoid being trapped in an anthropocentric paradigm. This research adopts the conceptual frameworks of Actor-Network Theory and the Politics of Things developed by Bruno Latour to view the relationship between humans and nature in a broader and non-teleological context. The analytical methods used in this research are philosophical approaches and literature review. Both approaches are used to find the philosophical foundation of ecological religious discourse and its correlation with the Non-human Turn. The research results show that at the epistemic level, human subjectivity is crucial in determining attitudes toward the conceived reality. However, at the ontological level, there is a space untouched by human thought and consciousness, implying a postponement/suspension of moral judgment that is not final. In particular, in moral consensus, the actors involved also include non-human entities. Consequently, the understanding of the ideal attitude toward nature should use a phenomenological approach that focuses on the consequences of the objectification of the subject toward the world beyond itself.AbstrakArtikel ini membahas perbedaan antara wacana posthuman dan wacana nonhuman dalam konteks agama ekologis. Berbeda dengan wacana posthuman yang memiliki elemen teleologis, wacana nonhuman menekankan bahwa manusia berinteraksi dengan entitas nonhuman tanpa mencari transformasi manusia menjadi non-manusia. Artikel ini mengusulkan bahwa penting untuk memahami hubungan manusia dengan alam sebagai nonhuman agency, bukan sekadar sebagai entitas nonhuman. Hal ini bertujuan untuk merekonstruksi basis ontologis wacana agama ekologis agar tidak terperangkap dalam paradigma antroposentrisme. Penelitian ini mengadopsi kerangka pikir Actor-network Theory dan Political of Things yang dikembangkan oleh Bruno Latour untuk memandang hubungan antara manusia dan alam dalam konteks yang lebih luas dan tidak teleologis. Metode analisis yang digunakan dalam penelitian ini adalah pendekatan filsafat dan literature review. Kedua pendekatan ini digunakan untuk menemukan fondasi filosofis perihal wacana agama ekologis dan korelasinya dengan Non-human Turn. Adapun hasil penelitian menunjukkan bahwa di level epistemik, subjektivitas manusia krusial dalam penentuan sikap terhadap realitas yang dikonsepsikan. Namun, di level ontologis, ada ruang sisa yang tak terjamah oleh pikiran dan kesadaran manusia yang mengimplikasikan adanya penundaan/ penangguhan moral judgement sehingga tidak bersifat final. Terutama, di dalam konsensus moral, aktor yang terlibat juga mencakup entitas non-human. Konsekuensinya, pemahaman tentang ideal sikap terhadap alam semestinya menggunakan pendekatan fenomenologis yang berfokus pada konsekuensi objektivikasi subjek terhadap dunia di luar dirinya.